Purification of Bacteriocin from Lactobacillus plantarum IIA-1A5 Grown in Various Whey Cheese Media Under Freeze Dried Condition - R. Fatmarani; I. I. Arief; C. Budiman (Faculty of Animal Science, Bogor Agricultural University, 2018)
Lactobacillus plantarum IIA-1A5 is a lactic acid bacteria (LAB) that has been reported to have capacity to produce bacteriocin, usually called plantaricin. This bacteriocin is usually produced in commercial synthetic media. However, the media is expensive, thus finding a novel source which is less expensive and abundant is necessary. The present work was aimed to compare the use of gouda and mozarella cheese whey as growth media of L. plantarum IIA-1A5 producing plantaricin, as well as to evaluate the effectiveness of freeze dried plantaricin as an antimicrobial agent. The results showed that gouda and mozarella cheese whey were applicable for growth media of L. plantarum IIA-1A5 and production of plantaricin. The plantaricin produced from the whey showed a size of about 9.6 kDa. Freeze dried plantaricin was shown to be relatively stable in the second week of storage, but there was a slight decrease in protein concentration during storage, indicating that the protein was partially denatured and precipitated. However, the freeze dried plantaricin showed inhibitory activities against S. aureus ATCC 25923, B. cereus ATCC 21332, S. thpymurium ATCC 14028, E. coli ATCC 25922, and P. aeruginosa ATCC 27853 during storage at room temperature.